Subclinical cardiac abnormalities in children with biliary atresia correlate with outcomes after liver transplantation - Li, Tingting; Wei, Xinzhe; Hao, Xiaoye; Ye, Xuying; Li, Chao; Li, Qi; Li, Zhuqing; Gao, Wei; Lu, Chengzhi (Frontiers in Pediatrics, 2023)
There are subclinical cardiac abnormalities (SCA) in children with biliary atresia (BA). However, data on the consequences of these cardiac changes after liver transplantation (LT) remain controversial in the pediatric field. We aimed to determine the relationship between outcomes and the subclinical cardiac abnormalities in pediatric patients with BA based on two-dimensional echocardiography (2DE) parameters. A total of 205 children with BA were enrolled in this study. The relationship between 2DE parameters and outcomes, including death and serious adverse events (SAE) after LT, was analyzed by regression analysis. Using receiver operator characteristic (ROC) curves to determine the optimal cut-off values of 2DE parameters for outcomes. Differences in the AUCs were compared using DeLong's test. The Kaplan–Meier method with log-rank testing was used to evaluate survival outcomes between groups. Left ventricular mass index (LVMI) and relative wall thickness (RWT) were found to be independently associated with SAE (OR: 1.112, 95% CI: 1.061–1.165, P ＜0.001 and OR: 1.193, 95% CI: 1.078–1.320, P =0.001, respectively). The cutoff value of LVMI for predicting the SAE was 68 g/m2.7 (AUC=0.833, 95% CI 0.727-0.940, P < 0.001), and the cutoff value of RWT for predicting the SAE was 0.41 (AUC=0.732, 95% CI 0.641-0.823, P < 0.001). The presence of subclinical cardiac abnormalities (LVMI ＞ 68 g/m2.7, and/or RWT ＞ 0.41) was associated with lower patient survival (1-year, 90.5% vs 100.0%; 3-year, 89.7% vs 100.0, log-rank P=0.001). and higher incidence of SAE events. Subclinical cardiac abnormalities were correlated with post-LT mortality and morbidity in children with BA. LVMI can predict the occurrence of death and serious adverse events after liver transplantation.